Combined effects of frailty status and cognitive impairment on health-related quality of life among community dwelling older adults. (March 2020) - Li, Chia-Lin; Chang, Hsing-Yi; Stanaway, Fiona F.
Highlights: Co-occurrence of frailty status with cognitive impairment is common in older adults. This co-occurrence is associated with worse HRQOL in older adults. Older adults with co-occurring frailty status and cognitive impairment may need more support for HRQOL. Abstract: Objectives: The aim of the present study was to investigate the combined association of frailty/pre-frailty and cognitive impairment with health related quality of life (HRQOL) among community dwelling older adults. Methods: Data came from a cross-sectional study of community-dwelling older adults aged 65 years or older, who participated in the 2013 National Health Interview Survey in Taiwan. Frailty was determined based on the Fatigue, Resistance, Ambulation, Illness, and Loss of weight (FRAIL) scale proposed by the International Association of Nutrition and Aging. The Mini-Mental State Examination was used to assess cognitive function. HRQOL was measured using the European Quality of Life-5 Dimensions questionnaire (EQ-5D) that assesses three levels of functioning for the dimensions of mobility, self-care, usual activities, pain/discomfort, and anxiety/depression. Poisson regression models were performed to estimate prevalence ratios (PR) and 95 % Confidence Intervals (95 % CI) for health problems in all EQ-5D domains. Results: In this study, 11.0 % of participants aged 65 years and older had co-occurring frailty/pre-frailty and cognitive impairment. After adjustment for other factors, compared with participants who were physically robust with normal cognition, participants with co-occurring frailty/pre-frailty and cognitive impairment had PRs of 10.38 (95 % CI 7.56–14.26), 9.66 (95 % CI 6.03–15.48), 9.37 (95 % CI 6.92–12.68), 3.04 (95 % CI 2.53–3.64), and 5.63 (95 % CI 3.83–8.28) for reporting problems with mobility, self-care, usual activities, pain/discomfort, and anxiety/depression, respectively. Conclusions: There is a high prevalence of co-occurrence of frailty/pre-frailty and cognitive impairment in older adults, and this co-occurrence was strongly associated with self-reported health problems across all EQ-5D domains.